A SPEECH-ACT ANALYSIS OF ANGER EXPRESSIONS IN TURNING RED MOVIE - Herawati, Rizki; Wiwoho, Gurendi (Universitas 17 Agustus 1945 Semarang, 2024)
Pragmatics is the branch of linguistics that deals with language in use and the contexts in which it is used. It encompasses phenomena including implicature, speech acts, relevance, and conversation, as well as non-verbal. One of the topics in pragmatics is speech acts. This research used a pragmatic approach. It is descriptive qualitative research, which takes the data from the dialogues in the movie entitled Turning Red that contain anger expressions. They were classified by using Mac Le Mouse’s classification of types of anger. This research aims to determine data regarding expressions of anger in the movie Turning Red. The data obtained becomes a sample to find out what meaning there is in the angry utterances in the dialogues between Mei Ling and Mother. There are 15 data of direct forms then 2 data of indirect forms. In addition, there are 7 types of anger that analyzed in this research. There are 4 data of judgmental anger, 4 data of volatile anger, 3 data of overwhelmed anger, 2 data of chronic anger, 2 data of self-inflicted, and 1 datum of paranoid anger. From the data analysis, daughter as the most dominant who tend to express direct form of anger. in addition, mother tend to express anger with direct and indirect. Key words: anger expression, script movie, speech act, speech functions,Turning Red..